Home Original Content Funny Pictures Funny GIFs YouTube Funny Text Funny Movies Channels Search

hide menu
What do you think? Give us your opinion. Anonymous comments allowed.
User avatar #221 - Acrylic (02/23/2011) [-]
x^2+6+9=x+3
x^2+6+9-x-3=0
x^2-x+12=0
x1=-(-1/2) - Square root of ((-1/2)+12)
x1=0.5 - 3.5
x1=-3
x2=-(-1/2) + Square root of ((-1/2)+12)
x2=0.5 + 3.5
x2=4
so x = 4 or -3
User avatar #225 to #221 - DrCommon (02/23/2011) [-]
is that you final answer
User avatar #226 to #225 - Acrylic (02/23/2011) [-]
NO it's wrong ;D
 Friends (0)